Analysis of Challenges in Using Google Classroom for Teaching English in Grade 2 at SMAN 4 Palu - Caharia Sentika, Caharia Sentika; Ana Kuliahana, Ana Kuliahana; Dzakiah, Dzakiah (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2023)
This research aims to find out the problems faced by teachers in using Google Classroom at grade two students of SMAN 4 Palu. The research problems are what is the problem faced by the teacher in using Google Classroom in English lessons? And how to solve the problem of Google Classroom in English lessons? This study used qualitative descriptive. The informants in this study were the principal, two English teachers, and 10 second-grade students. The data collection techniques were interviews and documentation. The result shows that the main problem faced by the teachers in using google classroom are: (1) A limited set of features that make it difficult for teachers to teach speaking and listening skills. (2) The teacher has problems in correcting students’ assignments, especially for reading and writing skills because there is no room for it. Therefore, the teachers have turned to other applications such as WhatsApp and Google Meet to support the ongoing learning process in Google Classroom, especially in teaching speaking and listening skills.